2011
DOI: 10.1080/00222348.2010.497465
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roller Speed, Die Temperature, Volumetric Flow Rate, and Multiple Extrusions on Mechanical Strength of Molten and Solidified LDPE under Tensile Deformation

Abstract: An experimental rig coupled with a high speed data-logging and recording system and a personal computer was specially designed and constructed for the real-time measurement of mechanical strength (in terms of drawdown force) as a function of volumetric flow rate and roller speed for virgin low-density polyethylene (LDPE) and reprocessed LDPE during a filament stretching process. The effect of the number of extrusion passes for the reprocessed LDPE was our main interest. The experimental rig was connected to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 24 publications
4
12
0
Order By: Relevance
“…For any given roller speed, the drawdown force increased with increasing volumetric flow rate in the extruder from 1.4 × 10 −7 to 4.1 × 10 −7 m 3 /s. This observation was in line with the work of Gupta and Bhattacharya [9] and our previous work [5, 29]. Higher volumetric flow rate was referred to as greater energy input or storage in the deformable polymer melts.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…For any given roller speed, the drawdown force increased with increasing volumetric flow rate in the extruder from 1.4 × 10 −7 to 4.1 × 10 −7 m 3 /s. This observation was in line with the work of Gupta and Bhattacharya [9] and our previous work [5, 29]. Higher volumetric flow rate was referred to as greater energy input or storage in the deformable polymer melts.…”
Section: Resultssupporting
confidence: 90%
“…As for the effect of volumetric flow rate from the extruder, it was found that the roller speed to failure for neat LDPE and wood/LDPE composites changed with changing volumetric flow rate. Higher volumetric flow rate contributed to greater average drawdown force and drawdown time because of the greater energy inputs given from the extruder [5, 29]. This behavior and its explanation are similar to those given for the LLDPE/LDPE blend system.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The most widely used and important device for the melt strength and transient extensional viscosity measurements is so‐called “Rheotens” 7–9. Recently published works by Sombatsompop et al10–12 proposed an experimental device which was specially designed and constructed in a similar fashion to the Rheotens to determine the melt strength online in a single screw extruder using a wide range of polymer systems including homopolymers,10, 11 polymer blends and composites12 and processing and reprocessing conditions 10, 11. They suggested that the drawdown force of molten LDPE was dependent on volumetric flow rate, die temperature, roller speed, take‐up style, and the number of extrusion passes.…”
Section: Introductionmentioning
confidence: 99%